Antibiotic prescribing practices in various periodontal surgeries in vicinity of Nagpur City: A survey - Grishmi Niswade; Deepti Gattani; Suresh Ughade (Wolters Kluwer Medknow Publications, 2021)
Background: Among the postoperative complications following periodontal surgery, the risk of infection stands out the most since infection of the surgical site can lead to poor surgical outcomes in terms of wound healing. Aim: This study aims to evaluate antibiotic-prescribing practices for various periodontal surgeries in vicinity of Nagpur city. Materials and Methods: An anonymous survey was distributed to periodontists through Google forms. The survey questioned prescribing practices for various periodontal surgeries, the demographic data and place of practice of the clinician, rationale for prescribing or not prescribing antibiotics, and acceptability of guidelines. The survey consisted of 12 questions, 7 of which were questioned to the practitioners "In an otherwise healthy patient, would you prescribe antibiotics for a X procedure" where X included various periodontal surgeries. Response choices were limited to "In most cases yes, in most cases no and I do not perform this procedure." Results were analyzed using statistical software. Results: A total of 50 periodontists responded out of 98 who were contacted to participate in the survey with a response rate of 51%. Nearly 58% of practitioners had a predominant work setting of a dental college and 42% have a predominant work setting of private practice. Practitioners were significantly more likely to prescribe antibiotics all the periodontal surgical procedures. The most common rationale for prescribing antibiotics was to decrease the chances of developing an infection, whereas the most common rationale for not prescribing antibiotics was a healthy patient and based on current and previous literature. Nearly 66% of practitioners reported that they would follow the guidelines for antibiotic prescription if they were developed by American Academy of Periodontology (AAP). Bivariate analysis revealed that there is no significant role of other characteristics on the response of an individual. Even multivariate analysis does not reveal significance of baseline characteristics although it revealed that respondents working in a dental college are 2.15 times more likely to follow AAP guidelines as compared to private practitioners. Females are 1.64 times more likely to follow AAP guidelines as compared to males and respondents practicing inside Nagpur are 1.35 times more likely to follow AAP guidelines as compared to those practicing outside city. Conclusion: Practitioners are more likely to prescribe antibiotics in the majority of the periodontal surgical procedures despite the standard indications for prescription. This misuse can lead to numerous complications in treatment and development of antibiotic resistance. Based on these results, specific guidelines for the use of antibiotics suggesting a particular antibiotic to be used in a particular periodontal surgery and its duration is the need of the hour to prevent the overuse of antibiotics.